A Simple Note on Informational Cascades - Annamaria Fiore; Andrea Morone (Kiel Institute for the World Economy (IfW), 2007)
Seminal models of herd behaviour and informational cascades point out existence of negative information externalities, and propose to ?destroy? information in order to achieve social improvements. Although in the last years many features of herd behaviour and informational cascades have been studied, this particular aspect has never been extensively analysed. In this article we try to fill this gap, investigating both theoretically and experimentally whether and to which extent destroying information can improve welfare. Our empirical results show that this decisional mechanism actually leads to a behaviour more consistent with the theory that in turn produces the predicted efficiency gain.
Keywords: C91; D62; 330; Informational cascades; information externality; individual decision making; experiment